PENINGKATAN KETERAMPILAN SOSIAL MELALUI TARI KREASI PADA ANAK KELOMPOK B DI TK KARTIKA X-6 PUSLATPUR MARTAPURA OKU TIMUR - Tria Agustina; Sri Sumarni; hasmalena hasmalena (FKIP Universitas sriwijaya, 2017)
This study uses a classroom action research type with the title of research “Improvment Of Social Skills Through Dance Creations Of Children Group B In TK Kartika X-6 PUSLATPUR Martapura OKU East,” The purpose of research is to determine the existence of social skills improvement through dance creations in children group B in TK Kartika X-6 PUSLATPUR Martapura OKU East. The subjects used in this study are class B amounted to 8 boys, and 12 girls. The data collection using observation sheet and documentation. It is proven that the cycle I is higer than the pre cycle of the average percentage of social skills of children that is as many as 6 children (30%) whose social skills began to grow (MB), 10 children (50%) oleveloped as expected (BSH), and there are 4 children (20%). Developing very well (BSB). It is proven that cycle II is higer than cycle I with average percentage of children social skill that is as much as 2 child (10%) whose social skill begin to develop (MB), 5 children (25%) developed as expected (BSH), and 13 children (65%) developed very well (BSH). So it can be obtained that dance creations can improve the social skills of the group’s children B in TK Kartika X-6 PUSLATPUR Martapura OKU East.